Impact of 30 years precipitation regime differences on forest soil physiology and microbial assemblages - Chakraborty, Amrita; Zádrapová, Dagmar; Dvořák, Jakub; Faltinová, Zuzana; Žáček, Petr; Cajthaml, Tomáš; Korecký, Jiří; Roy, Amit (Frontiers in Forests and Global Change, 2023)
Anthropogenic disturbances and climate change affect abiotic and biotic environmental drivers in forest ecosystems. Global warming impacts the soil moisture content, thus influencing the diversity, abundance and functioning of soil microfauna. However, limited studies have been conducted to evaluate the impact of long-term variation in precipitation on soil microfauna. A better understanding of soil microfauna functioning under various precipitation regimes can aid in formulating better prediction models for assessing future climate change impacts. The present study uses a multi-omics approach to capture the variability in the total organic carbon (TOC), total nitrogen (TN), pH, metabolites, microbial biomass and function due to the difference in soil water content mediated by long-term precipitation (30 years) and soil texture differences in two Norway spruce seed orchards. Results showed a positive correlation between TOC, TN, extracellular enzyme activities (EEAs) and phospholipid fatty acids (PLFA) content with higher precipitation, whereas microbial diversity showed an opposite trend. A distinct metabolic profile was observed between the two forest soils. Furthermore, variance partitioning canonical correspondence analysis (VPA) revealed a higher contribution of TOC and TN in shaping the microbial communities than soil pH and conductivity in Norway spruce seed orchards. Our study generates field data for modeling the impact of long-term precipitation variance supplemented by soil texture on soil microbial assemblage and function in Norway spruce stands.